El maltrato infantil: análisis de derecho comparado entre Colombia y Argentina (2016)
The issue of child abuse and the rights of children as subjects of fundamental rights and hierarchically first state to require that the guarantee, respect, and promote addressed through one of the ways to make them effective, which is : the obligation of states to provide legal remedies for such purposes. The enforcement of these rights is a way to make real papers valid not only provisions of the law written on paper, the actual recognition of these rights is sought before the courts or courts of law and courts both at regional, national and international level , it is to an organization. So things as mentioned above to make this mandatory application to be effective it requires a rule of law that enacted the declaration and promote, ie an instrument. At the same time it requires a mechanism, institution, resources or actions for the respective complaints to the competent bodies. The study of the basic structure of comparative research type developing a respective historical, political, economic and social systems of different protection rights; then, agencies judiciary assigned or responsible for the protection of such proceeds to compare and then also analyze the legal instruments that enshrine the rights of children, both in the Argentina national country Colombia and at the internationally that regulates them, completed or developed earlier it proceeds to buy the different mechanisms by which the rights of children become enforceable and applicable, with a major emphasis on actions or special resources of each country as compared . The comparative law analysis is completed and developed with the selection and analysis of cases that are considered a milestone or have generated a great brand in the jurisprudence as Argentina Colombia jurisprudence within different types of child abuse